Deletion of smn-1, the Caenorhabditis elegans ortholog of the spinal muscular atrophy gene, results in locomotor dysfunction and reduced lifespan. - Briese, M; Esmaeili, B; Fraboulet, S; Burt, E; Christodoulou, S; Towers, P; Davies, K; Sattelle, D (Oxford University Press, 2009)
Spinal muscular atrophy is the most common genetic cause of infant mortality and is characterized by degeneration of lower motor neurons leading to muscle wasting. The causative gene has been identified as survival motor neuron (SMN). The invertebrate model organism Caenorhabditis elegans contains smn-1, the ortholog of human SMN. Caenorhabditis elegans smn-1 is expressed in various tissues including the nervous system and body wall muscle, and knockdown of smn-1 by RNA interference is embryonic lethal. Here we show that the smn-1(ok355) deletion, which removes most of smn-1 including the translation start site, produces a pleiotropic phenotype including late larval arrest, reduced lifespan, sterility as well as impaired locomotion and pharyngeal activity. Mutant nematodes develop to late larval stages due to maternal contribution of the smn-1 gene product that allows to study SMN-1 functions beyond embryogenesis. Neuronal, but not muscle-directed, expression of smn-1 partially rescues the smn-1(ok355) phenotype. Thus, the deletion mutant smn-1(ok355) provides a useful platform for functional analysis of an invertebrate ortholog of the human SMN protein.